Guidelines for naming and studying plasma membrane domains in plants - Jaillais, Yvon; Bayer, Emmanuelle; Bergmann, Dominique C; Botella, Miguel A; Boutté, Yohann; Bozkurt, Tolga O; Caillaud, Marie-Cecile; Germain, Véronique; Grossmann, Guido; Heilmann, Ingo; Hemsley, Piers A; Kirchhelle, Charlotte; et al. (Nature plants, 2024)
Biological membranes play a crucial role in actively hosting, modulating and coordinating a wide range of molecular events essential for cellular function. Membranes are organized into diverse domains giving rise to dynamic molecular patchworks. However, the very definition of membrane domains has been the subject of continuous debate. For example, in the plant field, membrane domains are often referred to as nanodomains, nanoclusters, microdomains, lipid rafts, membrane rafts, signalling platforms, foci or liquid-ordered membranes without any clear rationale. In the context of plant-microbe interactions, microdomains have sometimes been used to refer to the large area at the plant-microbe interface. Some of these terms have partially overlapping meanings at best, but they are often used interchangeably in the literature. This situation generates much confusion and limits conceptual progress. There is thus an urgent need for us as a scientific community to resolve these semantic and conceptual controversies by defining an unambiguous nomenclature of membrane domains. In this Review, experts in the field get together to provide explicit definitions of plasma membrane domains in plant systems and experimental guidelines for their study. We propose that plasma membrane domains should not be considered on the basis of their size alone but rather according to the biological system being considered, such as the local membrane environment or the entire cell.
Keywords: buněčná membrána; rostliny; terminologie jako téma; membránové mikrodomény; Terminology as Topic; Membrane Microdomains; Plants; Cell Membrane